Efficient CO2 to CO electrolysis on solid Ni–N–C catalysts at industrial current densities. Issue 2 (4th January 2019) - Möller, Tim; Ju, Wen; Bagger, Alexander; Wang, Xingli; Luo, Fang; Ngo Thanh, Trung; Varela, Ana Sofia; Rossmeisl, Jan; Strasser, Peter
Abstract : We demonstrate the direct electrochemical conversion of CO2 to CO using solid state Ni–N–C carbon catalysts characterized by a coordinative molecular Ni–N x active moiety at industrial current densities of up to 700 mA cm −2 with faradaic efficiencies superior to those of the state-of-the-art AgO x electrocatalysts. Abstract : The electrochemical CO2 reduction reaction (CO2 RR) to pure CO streams in electrolyzer devices is poised to be the most likely process for near-term commercialization and deployment in the polymer industry. The reduction of CO2 to CO is electrocatalyzed under alkaline conditions on precious group metal (PGM) catalysts, such as silver and gold, limiting widespread application due to high cost. Here, we report on an interesting alternative, a PGM-free nickel and nitrogen-doped porous carbon catalyst (Ni–N–C), the catalytic performance of which rivals or exceeds those of the state-of-the-art electrocatalysts under industrial electrolysis conditions. We started from small scale CO2 -saturated liquid electrolyte H-cell screening tests and moved to larger-scale CO2 electrolyzer cells, where the catalysts were deployed as Gas Diffusion Electrodes (GDEs) to create a reactive three-phase interface. We compared the faradaic CO yields and CO partial current densities of Ni–N–C catalysts to those of a Ag-based benchmark, and its Fe-functionalized Fe–N–C analogue under ambient pressures, temperatures and neutral pH bicarbonate flows. Prolonged electrolyzer tests were conducted at industrial current densities of up to 700 mA cm −2 . Ni–N–C electrodes are demonstrated to provide CO partial current densities above 200 mA cm −2 and stable faradaic CO efficiencies around 85% for up to 20 hours (at 200 mA cm −2 ), unlike their Ag benchmarks. Density functional theory-based calculations of catalytic reaction pathways help offer a molecular mechanistic basis of the observed selectivity trends on Ag and M–N–C catalysts. Computations lend much support to our experimental hypothesis as to the critical role of N-coordinated metal ion, Ni–N x, motifs as the catalytic active sites for CO formation. Apart from being cost effective, the Ni–N–C powder catalysts allow flexible operation under acidic, neutral, and alkaline conditions. This study demonstrates the potential of Ni–N–C and possibly other members of the M–N–C materials family to replace PGM catalysts in CO2 -to-CO electrolyzers.